2008
DOI: 10.1002/pros.20883
|View full text |Cite
|
Sign up to set email alerts
|

Atlas of dihydrotestosterone actions on the transcriptome of prostate in vivo

Abstract: Our data support the idea that ARGs are essential for the normal development of the prostate and can also be responsible for the pathogenesis of the prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 79 publications
1
16
1
1
Order By: Relevance
“…In our study, we could show that mutations in the GARRPR motif that destroy binding to the BF-3 pocket did not inhibit AR-mediated gene expression but rather increased the expression of a subset of androgen-regulated genes mediating metabolic processes. Previous studies on AR-mediated up-regulation of genes involved in metabolism have pointed to a role of the AR in the normal prostate epithelium in driving the synthesis of seminal fluid (68,69). Therefore, our finding that the mutant Bag-1L increases the expression of AR-regulated genes involved in metabolism indicates a shift from the involvement of Bag-1L in promoting AR action in prostate cancer toward a normal prostate function.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In our study, we could show that mutations in the GARRPR motif that destroy binding to the BF-3 pocket did not inhibit AR-mediated gene expression but rather increased the expression of a subset of androgen-regulated genes mediating metabolic processes. Previous studies on AR-mediated up-regulation of genes involved in metabolism have pointed to a role of the AR in the normal prostate epithelium in driving the synthesis of seminal fluid (68,69). Therefore, our finding that the mutant Bag-1L increases the expression of AR-regulated genes involved in metabolism indicates a shift from the involvement of Bag-1L in promoting AR action in prostate cancer toward a normal prostate function.…”
Section: Discussionsupporting
confidence: 49%
“…7A). However, this was not the case for the Bag-1L (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) peptide, where only the exchange of the penultimate two amino acids XXXRPX to alanine decreased binding (Fig. 7B).…”
Section: Resultsmentioning
confidence: 86%
“…Similar to what we saw in LNCaP and LAPC4 cells, NCOR1 deletion in mouse prostate did not reduce AR mRNA levels. However, some of the AR target genes that are highly expressed in prostate epithelium (1, 47) lost their response to bicalutamide in mutant mice. In agreement with the previous report that Siah2 regulates gene expression by removing NCOR1 complexes from a sub-set of genes (1), Siah2 regulated AR target genes, ApoF , Nkx3.1, and Spink1 , lost their ability to respond to bicalutamide treatment in Ncor1 knockout mouse prostates, while Tmprss2 expression did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Time points were decided on the basis of previous transcriptomic studies [13,14], in which 3 h and 24 h time points had shown the highest transcriptional activity. The dose of DHT chosen, 0.1 mg, is the minimum dose needed to restore prostate size following castration in males [15], and has been previously administered as a physiological dose in other studies on both male and female mice [14,16,17]. However, further specifications are needed in the case of female mice, in which the DHT dose considered may result in supraphysiological circulating levels, at least in the first 6 hours after the injection.…”
Section: Sample Preparationmentioning
confidence: 96%